The legal status of the Arctic as a concept - Wojas, Jakub (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The Arctic is a place which generates widespread interest on the international stage. This region, which was seemingly forgotten after the end of the Cold War, has again become a place of great rivalry. The reason for this is primarily the shrinking of the Arctic ice cap, which has opened up the possibility of exploiting the region’s rich natural resources and using new, attractive, maritime routes. The problem which arises in connection with these possibilities is the lack of a specific legal status for this area. Arctic countries, in this case meaning the big five of the Arctic, which are the states which have direct access to the Arctic Sea: Denmark (via Greenland), Canada, Norway, Russia and the United States, have submitted their own proposals for the regulation of the legal regime around the North Pole. The most important issues are considered to be: the concept of sectors, the common heritage of humanity and the rule of law subjecting the Arctic sea. These three issues arise from different periods and though many of their elements are varied, they also have convergent points. It is likely that the status of this strategic area will be based on one of them.